Predictive Value of Circulating Pro-Fibrotic Cytokines for Progression in Idiopathic Pulmonary Fibrosis and Progressive Pulmonary Fibrosis (PPF): A Systematic Review and Meta-Analysis - Yolanda Julia Perel Putri; Indi Esha; Dewi Wijaya (HM Publisher, 2025)
Background: The clinical trajectory of patients with idiopathic pulmonary fibrosis (IPF) and the broader phenotype of progressive pulmonary fibrosis (PPF) is highly variable. Current prognostic models lack precision, highlighting an urgent need for reliable biomarkers. Circulating pro-fibrotic cytokines are implicated in fibrogenesis, but their individual predictive utility for disease progression remains debated. This systematic review and meta-analysis were conducted to synthesize the available evidence and quantify the predictive value of key circulating pro-fibrotic cytokines for disease progression in patients with IPF and PPF. Methods: A systematic literature search was performed in PubMed, Embase, and Scopus databases for studies published between January 1st, 2014, and December 31st, 2024. We included longitudinal cohort studies that evaluated the association between baseline circulating levels of Transforming Growth Factor-beta 1 (TGF-β1), Chemokine Ligand 18 (CCL18), or Interleukin-6 (IL-6) and a composite endpoint of disease progression (all-cause mortality, lung transplantation, or a significant decline in Forced Vital Capacity [FVC]). Hazard Ratios (HRs) and their 95% Confidence Intervals (CIs) were extracted. A random-effects model was used to pool the data. Heterogeneity was assessed using the I² statistic, and publication bias was evaluated with funnel plots and Egger’s test. Results: The search yielded 1,842 citations, from which seven studies comprising a total of 1,158 patients met the inclusion criteria. Elevated baseline levels of all three cytokines were significantly associated with an increased risk of disease progression. The pooled HR for TGF-β1 (4 studies, 650 patients) was 2.15 (95% CI: 1.55-2.98, p < 0.001), with moderate heterogeneity (I² = 55%). For CCL18 (5 studies, 812 patients), the pooled HR was 1.98 (95% CI: 1.41-2.78, p < 0.001), with substantial heterogeneity (I² = 68%). For IL-6 (3 studies, 515 patients), the pooled HR was 2.41 (95% CI: 1.78-3.26, p < 0.001), with low heterogeneity (I² = 21%). Subgroup analysis suggested a consistent predictive effect across both IPF and non-IPF PPF cohorts. Conclusion: This meta-analysis provides robust evidence that elevated circulating levels of TGF-β1, CCL18, and IL-6 are potent and independent predictors of disease progression in patients with IPF and PPF. These biomarkers hold significant promise for enhancing patient risk stratification, improving prognostic accuracy, and guiding personalized therapeutic decisions in clinical practice.